Graphene-Oxide-Assisted Biosensor With Optimum Response Selection Algorithm for Detecting and Quantifying Vimentin, a Potential Biomarker for Ovarian Cancer - Pandey, Ullas; Deshpande, Tushar; Agrawal, Amit; Singh, Shiv Govind (IEEE sensors letters, 2023)
Among gynecological malignancies, the mortality caused by ovarian cancer is the highest across the world, and this is primarily due to delay in the diagnosis owing to the limitations of traditional detection methods. This work proposes a facile, more sensitive, selective, and time-efficient device to detect and quantify vimentin protein, one of the potential biomarkers of ovarian cancer. The device is essentially a low-cost chemiresistive biosensor containing interdigitated electrodes (IDEs), which are fabricated on a printed circuit board substrate by sacrificial etching of copper. IDEs are decorated with graphene oxide and functionalized with a heterobifunctional linker to detect vimentin protein in diluted human blood plasma samples. The proposed biosensor is also equipped with a novel Python-based optimum response selection algorithm to find out the appropriate operating voltage interval where the sensor exhibits optimum response. The proposed biosensor exhibits a sensitivity of 19.528 KΩ( μ g/mL) −1 cm −2 and a low limit of detection of 0.956 pg/mL. The device also poses excellent selectivity and strong defiance toward nonbinding proteins and other interfering biomolecules. To the best of our knowledge, this is the first report of vimentin sensing by chemiresistive technique.